Bioprospecção de polissacarídeos sulfatados de macroalgas marinhas do litoral do Rio Grande do Norte: caracterização de uma heterofucana extraída da alga marron Sargassum filipendula que induz apoptose em células HeLa - Costa, Leandro Silva (2012)
The coast of Rio Grande do Norte has more than 100 species of seaweed, mostly unexplored regarding their pharmacological potential. The sulfated polysaccharides (PS) are by far the more seaweed compounds studied, these present a range of biological properties, such as anticoagulant activity, anti-inflammatory, antitumor and antioxidant properties. In this study, we extract sulfated polysaccharide rich-extracts of eleven algae from the coast of Rio Grande do Norte (Dictyota cervicornis; Dictiopterys delicatula; Dictyota menstruallis; Dictyota mertensis; Sargassum filipendula; Spatoglossum schröederi; Gracilaria caudata; Caulerpa cupresoides; Caulerpa prolifera; Caulerpa sertularioides e Codim isthmocladum), and these were evaluated for the potential anticoagulant, antioxidant and antiproliferative. All polysaccharide extracts showed activity for anticoagulant, antioxidant and/or antiproliferative activity, especially D. delicatula and S. filipendula, which showed the most prominent pharmacological potential, thereby being chosen to have their sulfated polysaccharides extracted. By fractionating method were obtained six fractions rich in sulfated polysaccharides to the algae D. delicatula (DD-0,5V, DD-0, 7V, DD-1,0v, DD-1,3v, DD-1,5v and DD-2,0) and five fractions to the alga S. filipendula (SF-0,5V, SF-0,7V, SF-1,0v, SF-1,5v and SF-2,0v). For the anticoagulant assay only the fractions of D. delicatula showed activity, with emphasis on DD-1, 5v that presented the most prominent activity, with APTT ratio similar to clexane® at 0.1 mg/mL. When evaluated the antioxidant potential, all fractions showed potential in all tests (total antioxidant capacity, hydroxyl and superoxide radicals scavenging, ferrous chelation and reducing power), however, the ability to chelate iron ions appears as the main mechanism antioxidant of sulfated polysaccharides from seaweed. In antiproliferative assay, all heterofucanas showed dose-dependent activity for the inhibition of cell proliferation of HeLa, however, with the exception of SF-0,7V, SF- 1,0v and SF-1,5v, all fractions showed antiproliferative activity against MC3T3, a normal cell line. The heterofucana SF-1,5V had its antiproliferative mechanism of action evaluated. This heterofucan induces apoptosis in HeLa cells by a pathway caspase independent, promoting the release of apoptosis Inducing Factor (AIF) in the cytosol, which in turn induces chromatin condensation and DNA fragmentation into 50Kb fragments. These results are significant in that they provide a mechanistic framework for further exploring the use of SF-1.5v as a novel chemotherapeutics against human cervical cancer.